Hak Pilih Kelompok Penyandang Disabilitas Dalam Pemilihan Umum Tahun 2019 Di Sumatera Barat - Henny Andriani; Feri Amsari (The Constitutional Court of the Republic of Indonesia, 2021)
In the voting process at elections, the people who vote in the elections believe they can influence the actions of those who are authorized to make binding decisions. In other words, they believe that what they are doing has a political effect (political efficiency). So it is an important thing to protect the political rights of all citizens, including the voting rights owned by groups of people with disabilities. Based on the above background, there are at least two problem formulations that can be used as a fence in this research, namely What are the problems and violations of the rights of groups of persons with disabilities in the 2019 General Election ?; and How are the rights of groups of persons with disabilities protected in the 2019 General Election in West Sumatra?